Pampas fox (Lycalopex gymnocercus) new intermediate host of Sarcocystis svanai (Apicomplexa: Sarcocystidae). Issue 3 (June 2017) - Scioscia, Nathalia P.; Olmos, Leandro; Gorosábel, Antonella; Bernad, Lucía; Pedrana, Julieta; Hecker, Yanina P.; Gual, Ignacio; Laura Gos, M.; Denegri, Guillermo M.; Moore, Dadín P.; Moré, Gastón
Abstract: Several Sarcocystis spp. have carnivores as definitive host and sarcocysts are common in muscles of herbivores (intermediate host). However, sarcocysts have been found in muscles of wild and domestic carnivores suggesting they are intermediate host for some Sarcocystis spp. Here, we report mature sarcocysts in the muscles of Pampas fox ( Lycalopex gymnocercus ). A total of 36 free-living foxes were analyzed. Different skeletal muscles were assessed by microscopic and molecular methods. Cysts and/or DNA of Sarcocystis sp. were detected in 61.1% (22/36) foxes. Histopathology revealed the presence of sarcocysts in 52.8% (19/36) foxes. The tongue and masseter were the muscles more frequently infected. Of all the samples processed by homogenization of pooled muscles of each animal, 45.4% (10/22) evidenced muscle cysts and 68.2% (15/22) resulted positives by PCR. Individual cysts obtained from the ten positive samples in direct microscopic examination were all positive by PCR. Five amplicons from individual cysts from different samples were selected for sequencing together with four PCR products obtained from the pooled muscles. All nine sequences shared a high identity among them (99.8–100%) and showed the highest identity by BLAST (99%) with a S . svanai sequence (KM362428) from a North American dog. By transmission electron microscopy, the sarcocyst wall was thin (< 1 μm), had minute undulations, with tiny evaginations and without evident villar protrusions. The cyst wall type is referred as "type 1". Sarcocystis svanai infects L . gymnocercus with a high prevalence and the presence of mature sarcocysts suggests the role of the Pampas fox as natural intermediate host. The definitive host of S . svanai remains unknown. Graphical abstract: Highlights: Few sarcocysts have been found in muscles of wild and domestic carnivores. Morphological and molecular description of sarcocysts in Lycalopex gymnocercus muscles was achieved. The mature sarcocysts characterization indicates that L . gymnocercus is a natural intermediate host of Sarcocystis svanai . Sarcocystis svanai infects L . gymnocercus with a high prevalence.